Topical 0.3% ciprofloxacin, norfloxacin, and ofloxacin in treatment of bacterial keratitis: a new method for comparative evaluation of ocular drug penetration. Issue 6 (June 1995) - Diamond, J P; White, L; Leeming, J P; Bing Hoh, H; Easty, D L
Abstract : AIMS--This study was designed to assess the relative corneal penetration of topical drops of three antibiotics and to relate those levels to minimum inhibitory concentrations for organisms associated with bacterial keratitis. METHODS--Four drops of each of ciprofloxacin, norfloxacin, and ofloxacin (0.3% topical ophthalmic preparations) were given to 12 patients undergoing corneal transplantation. After the recipient tissue was removed, corneal drug penetration was measured using high performance liquid chromatography. RESULTS--Intracorneal concentrations of ofloxacin (geometric mean 0.81 mg kg-1) were significantly higher than both ciprofloxacin (0.60 mg kg-1; p = 0.048) and norfloxacin (0.54 mg kg-1; p = 0.012). Ciprofloxacin and norfloxacin concentrations did not differ significantly (p = 0.33). CONCLUSIONS--Review of the minimum inhibitory concentrations of the fluoroquinolones against ocular pathogens reveals that ciprofloxacin is more potent than ofloxacin against many bacteria; ofloxacin is in turn more potent than norfloxacin. These data favour the selection of ciprofloxacin and ofloxacin rather than norfloxacin for the empirical treatment of corneal infection. The greater potency of ciprofloxacin offsets the superior penetration of ofloxacin. There is a need for improved clinical trial data concerning the use of fluoroquinolone eyedrops in ulcerative keratitis; some encouraging data are available for ciprofloxacin but not (in humans) for norfloxacin or ofloxacin.